Root Activity and Antioxidant Enzyme Activities of Rice Cultivars under Different Iron Toxicity Mitigation Options - A.K. Nayak, Rahul Tripathi, J. Meher, B. Lal; Priyanka Gautam, Mohammad Shahid, A.K. Shukla (Journal of the Indian Society of Soil Science, 2017)
Iron (Fe) toxicity is a widespread environmental problem of rice growing area in many parts of the world. Amendments and genotypes can be used to mitigate the Fe toxicity. Several strategies may be adopted by higher plants to cope up with high levels of soluble Fe in their environment. A field experiment was carried out in acidic laterite soil having 400 mg kg-1 di-ethylene tri-amine-penta-acetic acid extractable Fe (DTPA-Fe) to assess the root activity and antioxidant enzyme activities of rice cultivars under different soil management options in Fe toxic soil. The treatments comprised of four cultivars (two each tolerant and susceptible) and six amendments. The amendments resulted into the increase in soil pH as compared to the control, which helps in mitigation of Fe toxicity. Tolerant cultivars recorded significantly higher rice root oxidation and Fe plaque deposition as compared to sensitive cultivars under all the soil management treatments. Cultivars also differed significantly in the amount of Fe plaque on the roots under control. Iron concentration in the roots showed a reverse trend as compared to Fe oxidation and Fe plaque for all the cultivars and soil management treatments. Under high toxic Fe level (control), due to high activity of peroxidase (POD), catalase (CAT) and superoxide dismutase (SOD) mechanisms of antioxidative defense were more active for tolerant cultivars as compared to susceptible cultivars. The effect of defense mechanism of the tolerant cultivars is manifested in yield and under control condition, higher yield were reported for tolerant cultivars as compared to susceptible. Lime application is the most effective way to overcome the Fe toxicity, which increased the yield of both the tolerant and susceptible rice cultivars. Rice roots plays important role in alleviating the Fe toxicity by oxidizing the Fe2+ and excluding its uptake. Iron resistance of the tolerant cultivars is also attributed to the comparatively high levels of POD, CAT, and SOD activities in the leaf tissues. The differential response of the cultivars to the Fe-toxicity is due to differential ability of Fe compartmentation, root oxidation power and ability of cultivars to produce antioxidative stress enzymes. The mechanisms of Fe toxicity tolerance both in plant and soil are result of combined effect of genetics of the crop plant and management interventions.